Summary Record of Second Development Commissioners Conference on Community Projects (16th to 19th April 1953) - Planning Commission (Planning Commission, 1953)
I have been asked to explain briefly the aims and objects of the National Extension Organisation and Community Projects. You have no doubt read the speech the Prime Minister made when he presented the report of the Planning Commission to Parliament. In it, he explained that the Plan should not be regarded as consisting of a series of projects and works recommended for execution all over the country, but, he went on to say : "It is something much vaster....... the mighty scene of a nation building itself—all of us working together to make a new India, not abstractedly for a nation, but for the 360 million people." I should like you to bear this human aspect in mind. The Plan embodies the efforts of a great nation to rebuild itself, the millions of people in India working for a new life.
Government of India Planning Commission
Government of India Planning Commission